“NATIONAL UNITY AND SOLIDARITY” THEMED METAPHORICAL STRUCTURES IN THE ELECTION SONGS OF THE JUSTICE AND DEVELOPMENT PARTY IN 2015 GENERAL ELECTIONS - Gülcan IŞIK (International Journal of Eurasia Social Sciences, 2017)
As the most important communication element, when it comes to art creations, the language reveals its mission as a polyphonic and multifunction element apart from dsolay informative features. As artistic communication context, language emerges with a multifaceted deepened function. Now that the world’s meaning passes through artistic comment, when we take into consideration its pleasurable aspect occurring in the language with sanctified images and aesthetic as its artistic aspect, we witness a very effective communication network. At this point music is, too, a branch of art that serves for formation and strengthening a wide variety of various senses and principles, from a society’s social life to its political structure, from its inner world to its perception of life, from general customs to religious beliefs. Therefore, it is also possible to say music is an important ideological element. Form past to present political parties, during their political communication activities, have used and still use various means and methods in order to influence the voters and make them vote. In recent years, the election songs which the political parties attach great importance to and effectively benefit from emerge as a pretty effective communication method. Metaphor, taken usually as a linguistic subject, has become a work experienced at different fields by latest researchers from the aspect of intellectual process dragging human mind. In this study, metaphoric structures in the election songs which are effective methods in terms of propaganda of political communication shall be analyzed. With a view that the election songs and metaphoric meanings have manipulative effect on voters, this study is limited to the election songs used by the Justice and Development Party in 2015 general elections. The analysis has focused on the semantic manifestations of metaphoric structures themed “national unity and solidarity” in the election songs of the said party. Accordingly, it has been concluded that the theme have been frequently used and in this sense the party has tried to show that it is the party of whole Turkey.